Stress distribution of 12 μm thick crack free continuous GaN on patterned Si(110) substrate. Issue 3 (21st December 2012) - Hossain, T.; Wang, J.; Frayssinet, E.; Chenot, S.; Leroux, M.; Damilano, B.; Demangeot, F.; Durand, L.; Ponchet, A.; Rashid, M. J.; Semond, F.; Cordier, Y.; et al.
Abstract The stress distribution on crack free thick continuous GaN film (12 µm) grown by Metal organic chemical vapour deposition (MOCVD) on the arrays of different sizes of the patterned silicon substrate is investigated by micro‐Raman (µRaman) spectroscopy. On the largest crack free mesa (400 μm) both µ‐photoluminescence (µPL) at low temperature and µRaman measurements are performed. The µRaman shift of the GaN E2 mode shows the U‐shape in‐plane stress distribution across the mesa. The center of the mesa is under tensile stress and it relaxes near the corner and edges. A similar trend is observed also from the µPL spectra. The size of the mesa, the trench height and the trench width of the patterned silicon are varied to study the stress of the thick epitaxial crack free GaN layer. The size and trench height of the mesa have a large influence on the GaN film stress but the trench width does not show any significant effect. The maximum stress is saturated for the large sizes of mesas. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)